Responses of congeneric freshwater fish, Squalius carolitertii and Sequalius torgalensis, to future climate change - Jesus, Tiago Filipe Salgueiro de, 1987- (2018)
Tese de doutoramento, Biologia (Biologia Evolutiva), Universidade de Lisboa, Faculdade de Ciências, 2017